2008
DOI: 10.1111/j.1600-0781.2008.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Solar urticaria treated successfully with intravenous high‐dose immunoglobulin: a case report

Abstract: Solar urticaria is an idiopathic, chronic and rare photodermatosis, characterized by the sudden onset of pruritic urticarial hives and plaques on the exposed areas of the skin, after a brief period of exposure to the natural sunlight or to an artificial light source. A Caucasian 27-year-old man presented with clinical features suggestive of solar urticaria was referred to our photodermatology unit, where phototesting confirmed the diagnosis of solar urticaria induced by visible light. As he was refractory to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 3 publications
0
12
0
1
Order By: Relevance
“…Most squamous cell carcinomas and basal 314 cell carcinomas are found on the sun-exposed body sites [12] . Furthermore, many dermatoses, such as solar urticaria, actinic dermatitis, rosacea and lupus erythematosus, are induced or exacerbated by sun exposure [13][14][15] . Finally, photo-aging is another common clinical problem induced by sun exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Most squamous cell carcinomas and basal 314 cell carcinomas are found on the sun-exposed body sites [12] . Furthermore, many dermatoses, such as solar urticaria, actinic dermatitis, rosacea and lupus erythematosus, are induced or exacerbated by sun exposure [13][14][15] . Finally, photo-aging is another common clinical problem induced by sun exposure.…”
Section: Introductionmentioning
confidence: 99%
“…One case of severe solar urticaria remitted completely following a single infusion of IVIG administered in the dose of 2g/Kg [50]. Correia et al and Darras et al also reported on remission of severe solar urticaria in single patients following high dose IVIG infusion [51,52]. While the poor response seen in the one report by Llamas-Velasco et al, may have been due to differences in product or dosage protocol, it is also quite possible that solar urticaria is a heterogeneous disease, with Alters cellular recruitment [37,43] Limits complement activation and dampens complement-mediated vascular and tissue injury [37] Inhibits inflammatory cytokines and induces inhibitory cytokines By altering Th1/2 or Th17 maturation as well as modulating glucocorticoid receptors or Fcgamma receptors on T cells and inflammatory cells [34,42,44,45] or by inhibiting T cell activation [5,37] Decreased adhesion to endothelial cells [43] Adaptive Immunity…”
Section: Efficacy Of Ivig In Urticarial Syndromesmentioning
confidence: 89%
“…IVIG has been used in solar urticaria [22,23,[49][50][51][52]. Solar urticaria is characterized by development of urticarial eruption within a few minutes of exposure to ultraviolet radiation.…”
Section: Efficacy Of Ivig In Urticarial Syndromesmentioning
confidence: 99%
“…First‐line treatment with H1‐blockade and sun blockers may be enough for some patients, but induction of tolerance with an artificial UV source is sometimes recommended, in more severe cases (1). Other treatment options such as plasma exchange or photopheresis are based on the suspected existence of a circulating factor (2).…”
Section: Discussionmentioning
confidence: 99%